Earnest Money And its applications in Islamic banks - Ababneh, Omar Yousef (Journal of Economic, Administrative and Legal Sciences, 2021)
The final contracting stage between the two parties to the contract is preceded by an introductory stage required by the nature of the contract, especially those contracts that are completely related to the conclusion of other contracts, as is the case in the Murabaha contract of the ordering of the purchase and the lease ending with ownership and other complex contracts, which require special procedures appropriate to the types of risks related to them, which are arranged Certain obligations on the parties to the new contractual relationship, and this requires us to study and edit such similar forms.Among the most prominent practical pictures of these preliminary procedures is what is known as a contract with a deposit, or the first payment that is paid before the contract as a payment of the price, and what is known in the Islamic banks is what is known as the Earnest Money and it is not a single name, but each has its juristic conditioning and its special effects in terms of the motivation, purpose and legal conditioning. For her, therefore, this research comes to clarify the concept of Earnest Money and the reasons for it, the difference between it and the deposit and the down payment, as well as identify its applications in Islamic banks and legal adjustment to it, and the accounting method for dealing with it, and the research came out with some results and recommendations.
Keywords: margin of seriousness; down payment; legal conditioning; Islamic banks